From liability to asset: A large health system's approach to transforming hospital food - Sven Gierlinger; Bruno Tison; Nicole Giammarinaro (The Beryl Institute, 2022)
Historically, hospitals are infamous for poor food quality. Valuing food as a tenant of health and well-being, Northwell Health, New York's largest healthcare system, is transforming its hospital food program to become an asset and market competition differentiator. By focusing on structure, workforce, procurement and process, Northwell has improved patient experience performance "Quality of Food" by 61 percentile rank points within three years with minimal impact on budgetary cost. Experience Framework This article is associated with the Environment & Hospitality lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Environment%20%26%20Hospitality%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.